Initial description of the phylogeography, population structure and genetic diversity of Atlantic spotted dolphins from Brazil and the Caribbean, inferred from analyses of mitochondrial and nuclear DNA - Caballero, Susana; de O. Santos, Marcos C.; Sanches, Alexandra [UNESP]; Mignucci-Giannoni, Antonio A. (Elsevier, 2013)
We provide initial information regarding the population structure and genetic diversity of Stenella frontalis from the Caribbean and southeastern Brazil from analyses of mitochondrial control region sequences and sequences from the first intron of the α-lactalbumin gene. Comparisons with previously described S. frontalis sequences showed a high number of haplotypes shared between populations throughout their distribution range. High diversity was found for southeastern Brazil and Caribbean samples, and population structure analyses indicate significant differentiation among population units at the FST level, but not at the ΦST level. Significant differentiation at the FST level was found between the Caribbean population unit and all other populations units. These results suggest historical or present connectivity between the Azores and Madeira and the southeastern Brazil groups and population differentiation between the Caribbean and southeastern Brazil, supporting the notion of two separate stocks in the waters around the Atlantic coast of South America. © 2013 Elsevier Ltd.
Keywords: α-Lactalbumin; Atlantic spotted dolphin; Mitochondrial DNA; Phylogeography; Population structure; Stenella frontalis; connectivity; dolphin; genetic variation; phylogenetics; phylogeography; population distribution; population structure; species diversity; taxonomy; Azores; Brazil; Caribbean Islands; Madeira; Portugal